VLDL (Very-Low-Density Lipoprotein)-Apo E (Apolipoprotein E) May Influence Lp(a) (Lipoprotein [a]) Synthesis or Assembly - Croyal, Mikaël; Blanchard, Valentin; Ouguerram, Khadija; Chétiveaux, Maud; Cabioch, Léa; Moyon, Thomas; Billon-Crossouard, Stéphanie; Aguesse, Audrey; Bernardeau, Karine; Le May, Cédric; Flet, Laurent; Lambert, Gilles; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2020)
To clarify the association between PCSK9 (proprotein convertase subtilisin/kexin type 9) and Lp(a) (lipoprotein [a]), we studied Lp(a) kinetics in patients with loss-of-function and gain-of-function mutations and in patients in whom extended-release niacin reduced Lp(a) and PCSK9 concentrations. Approach and Results: Six healthy controls, 9 heterozygous patients with familial hypercholesterolemia (5 with low-density lipoprotein receptor [ ] mutations and 4 with gain-of-function mutations) and 3 patients with heterozygous dominant-negative loss-of-function mutations were included in the preliminary study. Eight patients were enrolled in a second study assessing the effects of 2 g/day extended-release niacin. Apolipoprotein kinetics in VLDL (very-low-density lipoprotein), LDL (low-density lipoprotein), and Lp(a) were studied using stable isotope techniques. Plasma Lp(a) concentrations were increased in -gain-of-function and familial hypercholesterolemia- groups compared with controls and -loss-of-function groups (14±12 versus 5±4 mg/dL; =0.04), but no change was observed in Lp(a) fractional catabolic rate. Subjects with -loss-of-function mutations displayed reduced apoE (apolipoprotein E) concentrations associated with a VLDL-apoE absolute production rate reduction. Lp(a) and VLDL-apoE absolute production rates were correlated ( =0.50; <0.05). ApoE-to-apolipoprotein (a) molar ratios in Lp(a) increased with plasma Lp(a) ( =0.96; <0.001) but not with PCSK9 levels. Extended-release niacin-induced reductions in Lp(a) and VLDL-apoE absolute production rate were correlated ( =0.83; =0.015). In contrast, PCSK9 reduction (-35%; =0.008) was only correlated with that of VLDL-apoE absolute production rate ( =0.79; =0.028). VLDL-apoE production could determine Lp(a) production and/or assembly. As PCSK9 inhibitors reduce plasma apoE and Lp(a) concentrations, apoE could be the link between PCSK9 and Lp(a).